The Impact of Diet on the Involvement of Non-Coding RNAs, Extracellular Vesicles, and Gut Microbiome-Virome in Colorectal Cancer Initiation and Progression - Ekine-Afolabi, Bene A.; Njan, Anoka A.; Rotimi, Solomon O.; R. I., Anu; Elbehi, Attia M.; Cash, Elizabeth; Adeyeye, Ademola (Frontiers in Oncology, 2020)
Cancer is the major cause of morbidity and mortality in the world today. The third most common cancer and which is most diet related is colorectal cancer. Although the link between diet and colorectal cancer remains complex and with limited understanding, Advancement in research methods have demonstrated the involvement of noncoding RNAs as key regulators of gene expression. MicroRNAs (miRNAs) which are a class of noncoding RMAs (ncRNAs) are key players in cancer related pathways in the context of dietary modulation. The involvement of non-coding RNA in cancer progression has recently been clarified throughout the last decade. ncRNAs are involved in biological processes relating to tumour onset and progression. The advances in research have given insights into cell to cell communication, by highlighting the pivotal involvement of extracellular vesicle associated-noncoding RNAs in tumorigenesis. The abundance & stability of extracellular vesicles (EV) associated non-coding RNAs act as a new diagnostic & therapeutic target for cancer. The understanding of the deranging of these molecules in cancer can give access to modulating the expression of the non-coding RNAs, thereby influencing the cancer phenotype. There are resident microbiota in the colon; to which the imbalance in the normal intestinal occurrence leads to chronic inflammation and the production of carcinogenic metabolites that lead to neoplasm This review discusses important dietary factors in relation to the expression of EV-associated non-coding RNAs in colorectal cancer, the impact of diet on the colon ecosystem with particular emphasis on interactions in the ecosystem and further emphasises on protective components such as polyphenols and pomegranates, as well as a focus on the molecular mechanisms in relation to prevention and/or treatment. Additionally, the bioactive dietary components that could re-sensitize treatment resistant cells are discussed.